Attitude Estimation from Vector Measurements: Necessary and Sufficient Conditions and Convergent Observer Design. Issue 1 (2023) - Yi, Bowen; Wang, Lei; Manchester, Ian R.
Abstract: The paper addresses the problem of attitude estimation for rigid bodies using (possibly time-varying) vector measurements, for which we provide a necessary and sufficient condition of distinguishability. Such a condition is shown to be strictly weaker than those previously used for attitude observer design. Thereafter, we show that even for the single vector case the resulting condition is sufficient to design almost globally convergent attitude observers, and an explicit design is obtained. To overcome the weak excitation issue, the design makes full use of historical information. Simulation results illustrate the accurate estimation despite with noisy measurements.